If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 5 = 4z Reorder the terms: 5 + 3z = 4z Solving 5 + 3z = 4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4z' to each side of the equation. 5 + 3z + -4z = 4z + -4z Combine like terms: 3z + -4z = -1z 5 + -1z = 4z + -4z Combine like terms: 4z + -4z = 0 5 + -1z = 0 Add '-5' to each side of the equation. 5 + -5 + -1z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1z = 0 + -5 -1z = 0 + -5 Combine like terms: 0 + -5 = -5 -1z = -5 Divide each side by '-1'. z = 5 Simplifying z = 5
| (9+n)x=21x | | -8(x-8)+9(2x+2)=9(x+8)-6 | | 8+8(4p-8)=8(3p-1) | | -5X+3Y+18=0 | | 25=15x-1.86x^2 | | 3x-8y=13 | | u^2-14u+45= | | x^4-41x^2=400 | | 8y-2=342 | | -12r+4=-15 | | 12+x=19 | | (3x+6)=(4x-17) | | -12r+4r=-15 | | 5(z+5)-(3+3z)=z | | y^2+9y+7=0 | | -25*-16=0 | | 5+(4+n)=5+(3+4) | | -5(2x+6)+4(9x+9)= | | 4x^4=81 | | 1-5n-2n=1 | | 2x+3=4x-21 | | 14-4(w-5)=6-2w | | (4x-17)=(3x+6) | | -4p-4p=-8 | | 2+4a=10q | | 6x^2-13x+60=0 | | 2q+4=10 | | x*50=1000 | | -2x+3=3(2x-1) | | 4p+3p=29 | | 4+x=25 | | 500+x=1200 |